POLIO ELIMINATION IN PAKISTAN: STILL A DREAM? - Mahmood, Hina (Journal of Ayub Medical College Abbottabad, 2018)
Pakistan has failed to achieve polio elimination till yet. Poliomyelitis is a crippling childhood disease, which causes paralysis for life. Aim of this study is to compare the frequency of polio cases in different provinces of Pakistan from 2010 till 2017. Results showed that total of 144 cases of polio were reported in 2010, a rise up to 198 was reported in 2011, a decline in cases was seen in 2012, i.e., 58, again cases rouse up to 93 cases, in 2013. In 2014, 306 cases were reported the rate declined considerably in 2015, i.e., 54 cases and in 2016 only 20 cases were seen. In 2017 only 8 cases were reported. So, it can be concluded that progressive improvement is seen in Pakistan regarding polio. Focused efforts should be continued till its complete elimination from the country as this will also give a positive message to the world about Pakistan being a responsible and peaceful nation. Keywords: Polio; Pakistan; Review; Eradiction